MODEL PENGELOLAAN DANA DESA BERBASIS SUSTAINABLE DEVELOPMENT GOALS (SDG’s) DESA - Mujalli; Syarif, Moh (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2024)
Village SDGs are an integrated effort to create villages without poverty and hunger, villages with an even economic growth, villages that care about health, villages that care about the environment, villages that care about education, women-friendly villages, networked villages, and culturally responsive villages to accelerate the achievement of the Sustainable Development Goals. This research aims to determine the Village Fund management model carried out by the Rongdalem Village government in realizing sustainable village development based on Village SDGs, as well as the results that have been achieved from the strategic plan that has been carried out. This research uses a qualitative descriptive research method. The data collection techniques used were interviews, documentation studies and observation. The research results show that the village fund management implemented is quite good and directed in accordance with the Village SDG's achievements. There are several problems in the management of Village Funds in realizing sustainable development based on Village SDGs, namely that the socialization carried out by the village government has not yet reached ordinary people, so there are still some people who do not understand the Village SDGs program. In conclusion, the implementation of village fund management in realizing sustainable development based on Village SDGs with the aim of overcoming poverty with an evenly growing economy carried out by the Rongdalem Village government, Omben District, Sampang Regency has shown quite good results because it has been directed and on target.